Aberrant inflammation in rat pregnancy leads to cardiometabolic alterations in the offspring and intrauterine growth restriction in the F2 generation. (20th December 2022) - Ushida, Takafumi; Cotechini, Tiziana; Protopapas, Nicole; Atallah, Aline; Collyer, Charlotte; Toews, Alexa J.; Macdonald-Goodfellow, Shannyn K.; Tse, M. Yat; Winn, Louise M.; Pang, Stephen C.; Adams, Michael A.; Othman, Maha; et al.
Abstract: Children of women with pre-eclampsia have increased risk of cardiovascular (CV) and metabolic disease in adult life. Furthermore, the risk of pregnancy complications is higher in daughters born to women affected by pre-eclampsia than in daughters born after uncomplicated pregnancies. While aberrant inflammation contributes to the pathophysiology of pregnancy complications, including pre-eclampsia, the contribution of maternal inflammation to subsequent risk of CV and metabolic disease as well as pregnancy complications in the offspring remains unclear. Here, we demonstrate that 24-week-old female rats (F1) born to dams (F0) exposed to lipopolysaccharide (LPS) during pregnancy (to induce inflammation) exhibited mild systolic dysfunction, increased cardiac growth-related gene expression, altered glucose tolerance, and coagulopathy; whereas male F1 offspring exhibited altered glucose tolerance and increased visceral fat accumulation compared with F1 sex-matched offspring born to saline-treated dams. Both male and female F1 offspring born to LPS-treated dams had evidence of anemia. Fetuses (F2) from F1 females born to LPS-treated dams were growth restricted, and this reduction in fetal growth was associated with increased CD68 positivity (indicative of macrophage presence) and decreased expression of glucose transporter-1 in their utero-placental units. These results indicate that abnormal maternal inflammation can contribute to increased risk of CV and metabolic disease in the offspring, and that the effects of inflammation may cross generations. Our findings provide evidence in support of early screening for CV and metabolic disease, as well as pregnancy complications in offspring affected by pre-eclampsia or other pregnancy complications associated with aberrant inflammation.